2012
DOI: 10.2174/138161212802651562
|View full text |Cite
|
Sign up to set email alerts
|

Protein-protein Interactions: Network Analysis and Applications in Drug Discovery

Abstract: Physical interactions among proteins constitute the backbone of cellular function, making them an attractive source of therapeutic targets. Although the challenges associated with targeting proteinprotein interactions (PPIs) -in particular with small molecules -are considerable, a growing number of functional PPI modulators is being reported and clinically evaluated. An essential starting point for PPI inhibitor screening or design projects is the generation of a detailed map of the human interactome and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 123 publications
0
12
0
Order By: Relevance
“…Targeting these non-hub nodes (with the exception of infectious diseases and cancer) is crucial to avoid unwanted side-effects. As opposed to targets of withdrawn drugs having a too large network influence, drug target proteins perturb the interactome in a controlled manner (Hase et al, 2009; Zhu et al, 2009; Butlinck et al, 2012; Yu & Huang, 2012). …”
Section: The Use Of Molecular Network In Drug Designmentioning
confidence: 99%
“…Targeting these non-hub nodes (with the exception of infectious diseases and cancer) is crucial to avoid unwanted side-effects. As opposed to targets of withdrawn drugs having a too large network influence, drug target proteins perturb the interactome in a controlled manner (Hase et al, 2009; Zhu et al, 2009; Butlinck et al, 2012; Yu & Huang, 2012). …”
Section: The Use Of Molecular Network In Drug Designmentioning
confidence: 99%
“…Network based drug discovery has become a recurrent theme for natural compounds too; characterization of the drug regulated genes and targets have been assisted greatly by computational techniques [7880]. Rational drug designing from natural sources have made drug costs and required resources to go down significantly over the years [8183]. Hence this study holds great implications for drug designing from natural products [8486].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the past few years, with the emergence of high-throughput technologies for omics data, like yeast 2 hybrid protein interactions, research of protein-protein interactions (PPI) has been occurring with high frequency. Bultinck et al [10] concluded that a growing number of functional PPI modulators are being reported and clinically evaluated. PPI provides us with more information for understanding the relationship between drug targets and other proteins in a systematic point of view.…”
Section: Introductionmentioning
confidence: 99%